Odpowiedź:
a)
[tex]8(x + 1) - 3(x - 6) = 2 (x - 2) \\ 8x + 8 - 3x + 18 = 2x - 4 \\ 8x - 3x - 2x = - 4 - 18 - 8 \\ 3x = - 30 \: \: | \div 3\\ x = - 10[/tex]
b)
[tex]2 - \frac{x - 4}{5} = \frac{x}{10} - x \: \: \: | \times 10 \\ 20 - 2x + 8 = x - 10x \\ - 2x - x + 10x = - 8 - 20 \\ 7x = - 28 \: \: | \div 7 \\ x = - 4[/tex]
c)
[tex] \frac{5}{7} t = 15 \: \: | \div \frac{5}{7} \\ t = 15 \times \frac{7}{5} \\ t = 21[/tex]
d)
[tex]9y - 14 = 4 + 3y \\ 9y - 3y = 4 + 14 \\ 6y = 18 \: \: | \div 6 \\ y = 3[/tex]
e)
[tex]3x(4x - 1) = 5 + 12 {x}^{2} \\ 12 {x}^{2} - 3x = 5 + 12 {x}^{2} \\ 12 {x}^{2} - 3x - 12 {x}^{2} = 5 \\ - 3x = 5 \: \: | \div ( - 3) \\ x = - \frac{5}{3} \\ x = - 1 \frac{2}{3} [/tex]